ABSTRACT STRATEGIES FOR INCREASING WATER SUPPLY AND SANITATION ACCESS SUSTAINABLE IN SLUMS AREAS BASED ON RISK LEVEL AND SETTLEMENT TYPOLOGY USING SWOT METHOD (CASE STUDY: PONTIANAK CITY, WEST KALIMANTAN PROVINCE) - Amala, Zulfa
The increasing population growth and the need for housing resulted in the emergence of slum settlements. In several cases in Indonesia, the development of settlements tends to be more directed towards areas on the banks of rivers. Likewise Pontianak City, has adaptive characteristics of riverside residents in physical, social and economic life to the river. Not to mention there are large ditches that are used by the community as housing and settlements on the water's edge. In general, these areas have the same problem, namely the provision of water and sanitation that is still not safe, one of the factors is financial limitations and public understanding of the importance of a healthy and quality environment. As a result, this study was carried out to determine the current state of clean water and sanitation infrastructure in Pontianak City's slum area, assess which infrastructure poses a risk to environmental health, determine priorities for improving clean water and sanitation infrastructure based on stakeholders, and finally plan a strategy to increase access to clean water and sustainable sanitation. The study focused on two types of slum typologies: one with a riverside typology in Panglima A. Rani and Kayu Manis, and the other with a lowland typology in RA Kartini. The current state of clean water and sanitation is as follows; in general, the community still uses untreated river and rainwater, most domestic wastewater discharges have only reached the most basic level of sanitation, there is still open defecation, a high risk of flooding caused by tides, and solid waste is dumped directly into rivers and/or burned. A sanitation risk index (SRI) was calculated using the Environmental Health Risk Assessment (EHRA) approach to estimate the present sanitation risk. SRI values were then obtained in places with riverside typology, such as Kayu Manis Area 382 (very high risk) and Panglima A Rani Area 370 (high risk), as well as lowland typology, such as RA Kartini Area 349 (high risk). These findings suggest that riverside areas have more risky management than lowland areas. ii When viewed from the sanitation risk, the order of priority is the domestic wastewater sector, drainage/puddles, Clean and Healthy Lifestyle, solid waste, and clean water. Meanwhile, stakeholder priorities were determined using the analytical hierarchy process (AHP) method, which showed different results. According to stakeholders, the priority for improvement was the provision of drinking water (30.3%), solid waste management (24.8%), domestic wastewater management (23%), and environmental drainage (21.8%). Furthermore, a SWOT analysis was carried out to obtain a strategy for increasing access to clean water and sanitation in the study location of the Pontianak City slum area, and some results were obtained. The priority should be put on improving facilities and infrastructure, drafting and enforcing regulations, outreach and training to the community, implementing the concept of Water Sensitive Urban Design (WSUD) in the area, improving the quality and performance management of drinking water companies, and increasing service capac